Semantic Guidelines and Conceptual Basis of a Social Education Teacher Professional Mobility in the Pedagogical Science - Nurzhanbayeva, Zhanat; Aidarov, Bakhtzhan; Baltabekova, Almagul; Makhmudov, Gavkharbek; Kamalov, Yusubaly; Seisen, Nayila (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article is dedicated to enhancing urgent scientific problems, which is considered the formation of professional mobility of future teachers of professional training as one of the main components of the modernization of their professional training system. The purpose of the article is to show the results of the scientific search for semantic guidelines and the structure of professional mobility of future teachers of professional training in the conceptual basis of pedagogical science. The main goal of this research paper was a kind of report on the author’s vision of the essence of professional mobility of future teachers in the structure of their professional readiness and scientific results, and acquaint readers with the opinion of scientists on the semantic guidelines and structure of professional mobility of future teachers based on a review of various information sources on selected topics; The leading idea of the publication of the article “Semantic guidelines and structure of professional mobility of a teacher in the conceptual basis of pedagogical science” is to share the experience of identifying the semantic guidelines and structure of professional mobility of future teachers of professional training. Then the concept of "the formation of professional mobility of future teachers of professional training" will be presented as a motivated, focused, and informed process of professional training, reflecting the dynamics of the development of its components and providing predicted changes, professional self-realization, and a quantitative increase in the indicators of the transition of subjects from a low level of mobility to a higher one by creating a system of pedagogical tools.